Transitional linkage: redesigning airport railway station with integrated MRT and BRT station - Rahman, Mohammad Zillur (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2017.